PENGARUH PENGGUNAAN MEDIA VISUAL BENTUK GRAFIK TERHADAP HASIL BELAJAR SEJARAH PADA MATERI POKOK KEHIDUPAN AWAL MANUSIA DI INDONESIA DI KELAS X SMA NEGERI 1 SIBABANGUN - ULINA SARI HHARAHAP (Jurnal TAROMBO, 2019)
The effect of using graphic visual media toward the resultof learning hystory on the begining of life in Indonesia at Tenth Grade Student in Class X SMA Sibabangun. The population in this study were all students of Class X SMA Negeri 1 Sibabangun which consists of one classes totaling 38 people. The sampling technique used is the Random Sampling. So that entire population can be sampled. Based on the calculation that the average value of 2,60 Strengthening administration. If the criteria are interpreted in the category of "Good". While the Learning Outcomes in Accounting Equation Topic has an average value of 76 is the "good" category. Analysis of the results obtained in testing the hypothesis t-test 2,330 and 1,688 ttable extent of freedom (df) = 38 -2 = 36 at 99% confidence level with an error rate of 5%. Thus it can be seen that t is greater than ttable namely >2,330, then the alternative hypothesis is accepted. The effect of using graphic visual media toward the resultof learning hystory on the begining of life in Indonesia at Tenth Grade Student in Class X SMA Sibabangun.